Effects of transport on a biomass burning plume from Indochina during EMeRGe-Asia identified by WRF-Chem - Lin, Chuan Yao; Chen, Wan-Chin; Chien, Yi-Yun; Chou, Charles C. K.; Liu, Chian-Yi; Ziereis, Helmut; Schlager, Hans; Förster, Eric; Obersteiner, Florian; Krüger, Ovid Oktavian; Holanda, Bruna A.; Pöhlker, Mira L.; et al. (Atmospheric chemistry and physics, 2023)
The Indochina biomass burning (BB) season in springtime has a substantial environmental impact on the surrounding areas in Asia. In this study, we evaluated the environmental impact of a major long-range BB transport event on 19 March 2018 (a flight of the High Altitude and Long Range Research Aircraft (HALO; https://www.halo-spp.de, last access: 14 February 2023) research aircraft, flight F0319) preceded by a minor event on 17 March 2018 (flight F0317). Aircraft data obtained during the campaign in Asia of the Effect of Megacities on the transport and transformation of pollutants on the Regional to Global scales (EMeRGe) were available between 12 March and 7 April 2018. In F0319, results of 1 min mean carbon monoxide (CO), ozone (O3), acetone (ACE), acetonitrile (ACN), organic aerosol (OA), and black carbon aerosol (BC) concentrations were up to 312.0, 79.0, 3.0, and 0.6 ppb and 6.4 and 2.5 µg m−3, respectively, during the flight, which passed through the BB plume transport layer (BPTL) between the elevation of 2000-4000 m over the East China Sea (ECS). During F0319, the CO, O3, ACE, ACN, OA, and BC maximum of the 1 min average concentrations were higher in the BPTL by 109.0, 8.0, 1.0, and 0.3 ppb and 3.0 and 1.3 µg m−3 compared to flight F0317, respectively. Sulfate aerosol, rather than OA, showed the highest concentration at low altitudes (<1000 m) in both flights F0317 and F0319 resulting from the continental outflow in the ECS. - - The transport of BB aerosols from Indochina and its impacts on the downstream area were evaluated using a Weather Research Forecasting with Chemistry (WRF-Chem) model. The modeling results tended to overestimate the concentration of the species, with examples being CO (64 ppb), OA (0.3 µg m−3), BC (0.2 µg m−3), and O3 (12.5 ppb) in the BPTL. Over the ECS, the simulated BB contribution demonstrated an increasing trend from the lowest values on 17 March 2018 to the highest values on 18 and 19 March 2018 for CO, fine particulate matter (PM2.5), OA, BC, hydroxyl radicals (OH), nitrogen oxides (NOx), total reactive nitrogen (NOy), and O3; by contrast, the variation of J(O1D) decreased as the BB plume's contribution increased over the ECS. In the lower boundary layer (<1000 m), the BB plume's contribution to most species in the remote downstream areas was <20 %. However, at the BPTL, the contribution of the long-range transported BB plume was as high as 30 %-80 % for most of the species (NOy, NOx, PM2.5, BC, OH, O3, and CO) over southern China (SC), Taiwan, and the ECS. BB aerosols were identified as a potential source of cloud condensation nuclei, and the simulation results indicated that the transported BB plume had an effect on cloud water formation over SC and the ECS on 19 March 2018. The combination of BB aerosol enhancement with cloud water resulted in a reduction of incoming shortwave radiation at the surface in SC and the ECS by 5 %-7 % and 2 %-4 %, respectively, which potentially has significant regional climate implications.